2010
DOI: 10.1186/1471-2458-10-672
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with motivation and hesitation to work among health professionals during a public crisis: a cross sectional study of hospital workers in Japan during the pandemic (H1N1) 2009

Abstract: BackgroundThe professionalism of hospital workers in Japan was challenged by the pandemic (H1N1) 2009. To maintain hospital function under critical situations such as a pandemic, it is important to understand the factors that increase and decrease the willingness to work. Previous hospital-based studies have examined this question using hypothetical events, but so far it has not been examined in an actual pandemic. Here, we surveyed the factors that influenced the motivation and hesitation of hospital workers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
133
5
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 131 publications
(157 citation statements)
references
References 21 publications
10
133
5
9
Order By: Relevance
“…2,7,[9][10][11][12][15][16][17]19 This study further identified a number of lesser-known factors that influence decisions to attend work during a disaster such as leadership in the workplace and the influence of positive collegial relationships.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,7,[9][10][11][12][15][16][17]19 This study further identified a number of lesser-known factors that influence decisions to attend work during a disaster such as leadership in the workplace and the influence of positive collegial relationships.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] Healthcare personnel who fear for their own safety in terms of illness, injury or death are reluctant to attend work during a disaster. [11][12][13][14] The availability of appropriate treatment, prophylaxis and infection control measures may increase the likelihood to respond.…”
Section: Concern For Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…HCW's hesitation and avoidance to work during viral pandemics has been reported before [8,10,16,17]. A survey of randomly selected HCWs across 3 health care trusts in West Midlands in the UK suggested that absenteeism can reach up to 85%, especially among nurses and ancillary healthcare workers during influenza pandemics [16].…”
Section: Discussionmentioning
confidence: 99%
“…A survey of randomly selected HCWs across 3 health care trusts in West Midlands in the UK suggested that absenteeism can reach up to 85%, especially among nurses and ancillary healthcare workers during influenza pandemics [16]. Imai et al reported that 14.7% of hospital employees in 3 core hospitals in Japan were very hesitant to work during the H1N1 pandemic [17]. This unwillingness was even higher among community nurses.…”
Section: Discussionmentioning
confidence: 99%